Neuropeptide S reduces fear and avoidance of con-specifics induced by social fear conditioning and social defeat, respectively. (September 2016) - Zoicas, Iulia; Menon, Rohit; Neumann, Inga D.
Abstract: Neuropeptide S (NPS) has anxiolytic effects and facilitates extinction of cued fear in rodents. Here, we investigated whether NPS reverses social fear and social avoidance induced by social fear conditioning (SFC) and acute social defeat (SD), respectively, in male CD1 mice. Our results revealed that intracerebroventricular NPS (icv; 10 and 50 nmol/2 μl) reversed fear of unknown con-specifics induced by SFC and dose-dependently reduced avoidance of known aggressive con-specifics induced by SD. While 50 nmol of NPS completely reversed social avoidance and reinstated social preference, 10 nmol of NPS reduced social avoidance, but did not completely reinstate social preference in socially-defeated mice. Further, a lower dose (1 nmol/2 μl) of NPS facilitated the within-session extinction of cued fear, while a higher dose (10 nmol/2 μl) reduced the expression of cued fear. We could also confirm the anxiolytic effects of NPS (1, 10 and 50 nmol/2 μl) on the elevated plus-maze (EPM), which were not accompanied by alterations in locomotor activity either on the EPM or in the home cage. Finally, we could show that icv infusion of the NPS receptor 1 antagonist D-Cys( t Bu) 5 -NPS (10 nmol/2 μl) did not alter SFC-induced social fear, general anxiety and locomotor activity. Taken together, our study extends the potent anxiolytic profile of NPS to a social context by demonstrating the reduction of social fear and social avoidance, thus providing the framework for studies investigating the involvement of the NPS system in the regulation of different types of social behaviour. Highlights: We use social fear conditioning and social defeat to induce social fear and avoidance. Neuropeptide S (NPS) reverses social fear and reduces social avoidance in male mice. We show for the first time a potent anxiolytic profile of NPS in social contexts.